The evolutions of microstructure in pressureless sintered silver die attach material - Omar, Ghazali; Esa, Siti Rahmah; Sheikh Md Fadzullah, Siti Hajar; Siow, Kim Shyong; Abdul Rahim, Bazura (Universiti Malaysia Perlis, 2021)
Sintered silver (Ag) is one of the most promising interconnect materials for high temperature electronics applications due to its potential to withstand harsh and extreme environments. This paper investigates the microstructure evolutions of Ag particles under pressureless sintering in a polymeric adhesive binder at 200 °C, 250 °C, 275 °C, and 300 °C for a duration of 2 hours. The grains, particles, and neck growth observed via two-dimensional Focused Ion Beam (FIB) cuts on the samples at different sintering temperatures were associated with the atomic motions and reduction of surface energy that is the driving force for sintering. In this study, the pressureless sintering process in a polymeric adhesive binder successfully transformed the scattered Ag particles into a compact and dense Ag joining at 300 °C. The electrical conductivity value obtained at 300 °C was 5.2E+05 S/cm, which was the highest among the evaluation samples.